Electrically responsive release of proteins from conducting polymer hydrogels. (1st March 2023) - Cheah, Ernest; Bansal, Mahima; Nguyen, Linh; Chalard, Anaïs; Malmström, Jenny; O'Carroll, Simon J.; Connor, Bronwen; Wu, Zimei; Svirskis, Darren
Abstract: Electrically modulated delivery of proteins provides an avenue to target local tissues specifically and tune the dose to the application. This approach prolongs and enhances activity at the target site whilst reducing off-target effects associated with systemic drug delivery. The work presented here explores an electrically active composite material comprising of a biocompatible hydrogel, gelatin methacryloyl (GelMA) and a conducting polymer, poly(3, 4-ethylenedioxythiophene), generating a conducting polymer hydrogel. In this paper, the key characteristics of electroactivity, mechanical properties, and morphology are characterized using electrochemistry techniques, atomic force, and scanning electron microscopy. Cytocompatibility is established through exposure of human cells to the materials. By applying different electrical-stimuli, the short-term release profiles of a model protein can be controlled over 4 h, demonstrating tunable delivery patterns. This is followed by extended-release studies over 21 days which reveal a bimodal delivery mechanism influenced by both GelMA degradation and electrical stimulation events. This data demonstrates an electroactive and cytocompatible material suitable for the delivery of protein payloads over 3 weeks. This material is well suited for use as a treatment delivery platform in tissue engineering applications where targeted and spatio-temporal controlled delivery of therapeutic proteins is required. Statement of significance: Growth factor use in tissue engineering typically requires sustained and tunable delivery to generate optimal outcomes. While conducting polymer hydrogels (CPH) have been explored for the electrically responsive release of small bioactives, we report on a CPH capable of releasing a protein payload in response to electrical stimulus. The composite material combines the benefits of soft hydrogels acting as a drug reservoir and redox-active properties from the conducting polymer enabling electrical responsiveness. The CPH is able to sustain protein delivery over 3 weeks, with electrical stimulus used to modulate release. The described material is well suited as a treatment delivery platform to deliver large quantities of proteins in applications where spatio-temporal delivery patterns are paramount. Graphical abstract: Image, graphical abstract